Physical–Chemical Exfoliation of n-Alkylamine Derivatives of Layered Perovskite-like Oxide H2K0.5Bi2.5Ti4O13 into Nanosheets - Iana A. Minich; Oleg I. Silyukov; Sergei A. Kurnosenko; Veronika V. Gak; Vladimir D. Kalganov; Petr D. Kolonitskiy; Irina A. Zvereva (Nanomaterials, 2021)
In the present work, we report the results on exfoliation and coating formation of inorganic–organic hybrids based on the layered perovskite-like bismuth titanate H2K0.5Bi2.5Ti4O13·H2O that could be prepared by a simple ion exchange reaction from a Ruddlesden–Popper phase K2.5Bi2.5Ti4O13. The inorganic–organic hybrids were synthesized by intercalation reactions. Exfoliation into nanosheets was performed for the starting hydrated protonated titanate and for the derivatives intercalated by n-alkylamines to study the influence of preliminary intercalation on exfoliation efficiency. The selected precursors were exfoliated in aqueous solutions of tetrabutylammonium hydroxide using facile stirring and ultrasonication. The suspensions of nanosheets obtained were characterized using UV–vis spectrophotometry, dynamic light scattering, inductively coupled plasma spectroscopy, and gravimetry. Nanosheets were coated on preliminarily polyethyleneimine-covered Si substrates using a self-assembly procedure and studied using atomic force and scanning electron microscopy.